Is Transparency Good for You, and Can the IMF Help? - Shin, Yongseok (IMF Working Papers; Working Paper ;, 2003)
This paper finds that reforms introduced by the IMF to promote transparency have created more informed markets and reduced borrowing costs for those emerging market countries that volunteered for them. Using a quarterly panel estimation with fixed country effects, we find that sovereign spreads fall following the adoption of three different transparency reforms. The effects are economically important, especially for those countries with low initial transparency. We use two-stage least squares to address any endogeneity in the timing of reforms exploiting internal IMF timetables that are unrelated to country events. Next, using a panel GARCH specification, we show that spreads move more than normal in the days immediately following publication of IMF country documents.